Analisis Kelayakan Finansial dan Strategi Pengembangan Teh Gaharu di Kabupaten Bangka Tengah (Studi Kasus: Teh Gaharu “Aqilla” Gapoktan Alam Jaya Lestari) - Eni Karsiningsih (Universitas Muhammadiyah Yogyakarta, 2016)
This study aims to analyze feasibility of agarwood tea business, to describe marketing strategies of agarwood tea, and to analyze the business development strategy of agarwood tea